Pengaruh Perencanaan Pajak, Penghindaran Pajak, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Syamsul Asmedi; Sulastri Sulastri (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Firm value is an important indicator that reflects a company’s performance and prospects, as well as serving as a basis for investors in making decisions. This study aims to examine the effect of tax planning, tax avoidance, and firm size on firm value in the property and real estate sector listed on the Indonesia Stock Exchange during the 2019–2023 period. This research employs a quantitative approach using secondary data, with the sample determined through purposive sampling, resulting in 10 companies with a total of 50 financial statement data. The analysis was conducted using panel data regression with Eviews 12 software. The results show that tax planning, tax avoidance, and firm size simultaneously affect firm value. However, partially, tax planning and tax avoidance have no significant effect on firm value, while firm size has a significant effect. These findings indicate that firm value is more influenced by the scale of the company’s operations rather than its tax management strategies. The implication of this study is that companies need to pay attention to business size growth in order to enhance firm value and attract investors.